FENOMENA KEKERASAN DALAM NOVEL DI TANAH LADA KARYA ZIGGY ZEZSYAZEOVIENNAZABRIZKIE - Ikki Pramatasari Kadir Ikki (JURNAL ILMU BUDAYA, 2021)
The Studi aims to the forms of violence the occurred in the novel Di Tanah Lada by Ziggy Zezsyazeoviennazabrizkie and to do with the social life. The method of collecting data used in this study, which is the method of study library. The library to read a number of books and writings that have to do white objects that will be investigated. This type of data used in this study is divided into two, namely the primary and the secondary. The results showed there was a picture of the violence experienced by the child and wife conducted by the character’s father as head of the family has to do with reality.